Current trends of unicompartmental knee arthroplasty (UKA): choosing between robotic-assisted and conventional surgeries and timing of procedures - Kelvin S. C. Cheung; Kai Chun Augustine Chan; Amy Cheung; Ping Keung Chan; Michelle Hilda Luk; Kwong Yuen Chiu; Henry Fu (Arthroplasty)
Abstract Background With robotic advancements in UKA technology, we sought to explore if robotic-assisted UKA could translate to clinical benefits such as reduced hospital stays and lowered emergency readmissions. Also, current utilization trends of UKA and choice of procedure timing (unilateral [uUKA] vs. one-staged bilateral UKA [biUKA]) could be explored. Methods This was a retrospective study utilizing the Clinical Data Analysis and Reporting System (CDARS) for data retrieval. All patients who had undergone primary UKA in all Hospital Authority (HA) hospitals in HK from 2021–2023 were included. Primary outcomes included utilization of UKA compared to TKA and percentage utilization of different UKA systems, namely, conventional, Mako, and Cori/Navio systems, from 2021–2023. Secondary outcomes involved: (1) patient demographics, (2) postoperative average length of stay (ALOS), (3) 30-day and 90-day postoperative Accident and Emergency Department (AED) attendance, (4) surgical times (skin-to-skin) and (5) 90-day mortality and reoperation. Differences in outcomes between uUKA and biUKA and between different robotic systems were examined. Regression analysis was performed to study if utilization of robotic-assisted systems could contribute to reduced hospital stays. Results UKA accounted for 15.2% of primary knee arthroplasties throughout 2021–2023. Robotic-assisted UKA (Mako and Navio/Cori) has shown an increasing utilization since 2022 in both unilateral (16.0% to 25.9%) and bilateral operations (17.8% to 29.0%). Mako had shorter ALOS than Navio/Cori (2.9 ± 1.6 vs. 3.6 ± 2.6 days; P = 0.006) and significantly shorter ALOS than conventional UKA (2.9 ± 1.6 vs. 3.6 ± 2.6 days; P = 0.004). Utilization of Mako was predictive of shortened ALOS on multi-linear regression (β = − 0.056; P = 0.049). Interestingly, biUKAs, especially conventional ones, showed a lower attendance rate than uUKAs at 30-day (2.9% VS 6.9%; P = 0.036) and 90-days (7.8% VS 15.7%; P = 0.004). Robotic-assisted surgery was associated with a prolonged surgical time of 16.4 min in uUKA and 29.1 min in biUKA compared to conventional operations. Conclusion UKA utilization has dropped since 2021 but the percentage of robotic-assisted UKA has risen. Mako yielded promising results in reducing hospital stays compared to conventional operations. Sub-group analysis (Mako versus Cori/Navio) highlighted the importance of distinguishing between different robotic platforms. For patients with bilateral unicompartmental OA, biUKA was shown to be a safe and effective alternative to unilateral operations. Trial Registration Registered (HKU/ HA HKW IRB; Ref No: 24–373).